2021
DOI: 10.3390/app11178170
|View full text |Cite
|
Sign up to set email alerts
|

A Real-Time BLE/PDR Integrated System by Using an Improved Robust Filter for Indoor Position

Abstract: Indoor position technologies have attracted the attention of many researchers. To provide a real-time indoor position system with high precision and stability is necessary under many circumstances. In a real-time position scenario, gross errors of the Bluetooth low energy (BLE) fingerprint method are more easily occurring and the heading angle of the pedestrian will drift without acceleration and magnetic field compensation. A real-time BLE/pedestrian dead-reckoning (PDR) integrated system by using an improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Those influences can be reduced successfully by implementing various filters, most commonly used are variations of the Kalman Filter [27] and Particle Filters [25]. Fingerprinting usually requires a calibration pre-operation, which can take tremendous time and effort; however, if done properly, it can achieve a positioning error of less than 1 m, especially if fused with other sensor data [28]. Frequently, this process requires to be repeated after some time, due to the changes in environment.…”
Section: Ble Indoor Localization Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those influences can be reduced successfully by implementing various filters, most commonly used are variations of the Kalman Filter [27] and Particle Filters [25]. Fingerprinting usually requires a calibration pre-operation, which can take tremendous time and effort; however, if done properly, it can achieve a positioning error of less than 1 m, especially if fused with other sensor data [28]. Frequently, this process requires to be repeated after some time, due to the changes in environment.…”
Section: Ble Indoor Localization Systemsmentioning
confidence: 99%
“…Xu et al [28] presented an IPS which combines the fingerprinting-based RSSI techniques with pedestrian dead reckoning (PDR). The fingerprinting method was improved by using robust filter, and the PDR was improved by using a Mahony complementary filter, which reduced the drift error.…”
Section: Ble Indoor Localization Systemsmentioning
confidence: 99%
“…The speed estimation research mainly includes step frequency detection and step length estimation [3]. Many step detection algorithms have been proposed by researchers, including peak detection, threshold setting, zero velocity update, autocorrelation and finite-state machine (FSM) [31]. This paper uses the peak detection method to detect a step.…”
Section: Speed Estimationmentioning
confidence: 99%
“…This paper uses the peak detection method to detect a step. Studies have shown that the step length is related to the acceleration, height, and strides of different people, and the step length estimated by different methods differs little [7,31]. In this paper, a nonlinear step length estimation algorithm is adopted, which takes the maximum and minimum acceleration of pedestrians within one step as the characteristic quantity.…”
Section: Speed Estimationmentioning
confidence: 99%
“…This leads to poor positioning accuracy. To realize indoor localization, extensive research has been carried out on various localization technology such as Wireless Fidelity (Wi-Fi) [2], Bluetooth [3], geomagnetism [4], Ultra-wideband (UWB) [5][6][7][8], pseudo-satellite [9]. Among these approaches, UWB has attracted extensive attention due to its large transmission bandwidth that leads to high localization accuracy resolution, which can meet the requirements of indoor highprecision positioning.…”
mentioning
confidence: 99%